Studi Pengaruh Elektrolit Nacl terhadap Baterai Elektroda Pb- Pb02 berbasis PV Sebagai Charging - Hafiz, Hafiz; Maizana, Dina; Mungkin, Moranain; Satria, Habib (Universitas Medan Area, 2024)
Research has been conducted on the study of the effect of NaCl electrolyte on Pb-PbO2 electrode batteries. So far, H2SO4 battery electrolyte can have a negative impact, one of which can irritate the skin, it will even become toxic when inhaled by humans. For this reason, I tried to replace the use of the H2SO4 electrolyte with NaCl electrolyte so that a voltage of 6.73 volts was obtained while the H2SO4 electrolyte reached a voltage of 12 volts with an electrolyte that was more environmentally friendly. Furthermore, the NaCl electrolyte will be developed to increase the voltage yield equal to the H2SO4 electrolyte.